An Examination of Pain's Relationship to Sleep Fragmentation and Disordered Breathing Across Common Sleep Disorders. Issue 8 (28th August 2017) - Mundt, Jennifer M; Eisenschenk, Stephan; Robinson, Michael E
Abstract: Objective: Short sleep duration and insomnia have been linked to higher pain and an increased risk of developing chronic pain, but relatively little research has examined the contribution of sleep disordered breathing (SDB) to pain. This study examined the unique contributions of SDB and insomnia to chronic pain. Subjects: Adult patients referred to an academic sleep center for overnight polysomnography were invited to participate. Methods: Participants (N = 105) completed questionnaires about their sleep and pain, including the Insomnia Severity Index, Medical College of Virginia Pain Questionnaire, and two weeks of sleep/pain diaries. Results: Most participants (80.00%) reported chronic pain, and the likelihood of having chronic pain did not differ by sleep disorder. However, there was a significant difference in pain intensity; individuals with comorbid obstructive sleep apnea (OSA)/insomnia reported an average pain intensity that was 20 points (out of 100) higher than individuals with insomnia or no diagnosis and 28 points higher than those with OSA, controlling for participant sex ( P s < 0.05). In a hierarchical regression, pain was unrelated to measures of sleep fragmentation (apnea-hypopnea index, spontaneous arousals, periodic leg movement arousals) and nocturnal hypoxemia (SaO2 nadir, time at or below 88% SaO2 ). Conclusions: Polysomnography measures of SDB severity and sleep fragmentation were unrelated to pain intensity. However, comorbid OSA/insomnia was associated with significantly higher pain (compared with either disorder in isolation), a finding that has implications for the treatment of chronic pain and possibly for understanding the mechanisms of chronic pain.